Reinventing The Role of Social Prophetic and Mass Consciousness Concept in Ali Syariati’s Liberation Theology - Richo Bintang Mahendra; Shofiyullah Muzammil; Ahmad Nurcholish (Aqlania, 2025)
One of Muslim intellectual who has a conception of the role of intellectuals as the basis of social transformation is Ali Syariati. Shariati states that intellectuals are the basis of social transformation. But on the other hand, Syariati considers mass consciousness as an important element for social transformation. This research largely attempts to reconstruct Syariati's thoughts on the concept of Rausyan Fikr as the basis of social transformation. In addition, this research also seeks to find a dialectical relationship between intellectuals and mass consciousness in Syariati's thought. The author wants to show that intellectuals and mass consciousness are two important elements that allow the birth of social transformation. This study uses literature-based qualitative research, using hermeneutic and dialectical analysis methods. The primary data used by Syariati's lectures titled On the Sociology of Islam and What is to be Done. The results shows that the social transformation can occur by the role of intellectuals (rausyan fikr) who perform prophetic duties (social prophet). In a social revolution, intellectuals are tasked with transferring all the social problems faced into the masses as well as providing an ideological foundation as a movement paradigm. However, with their free will, the masses can choose whether to accept or reject the agitation carried out by these enlightened intellectuals. The orientation for social transformation is the ummah society.Keywords: Social Prophetic, Mass Consciusness, Ali Syariati